(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
This paper discussed the importance of stem cells in the field of medical research because of the qualitative leap they make in the health field. The study of stem cells is still widespread and limited to certain countries due to their financial cost and the length of the study period. Stem cells are still specific to certain diseases such as diabetes and blood diseases, and there must be follow-up. And severe immune control in cases of stem cell division because they sometimes cause some tumors, some of which are under control. Stem cells are undifferentiated cells that have the ability to transform into one of the types of differentiated cells present in the body, which number more than 200, including Blood cells, nerve cells, muscle cells, heart cells, glandular cells, and skin cells. Some stem cells can be stimulated to transform into any type of cell in the body. While some stem cells are already partially differentiated, and are able to transform into only specific types. From nerve cells, stem cells multiply by dividing, and produce more stem cells, until they are stimulated to begin the process of differentiation. As they continue to divide, they become little by little more specialized until they lose their ability to turn into other cells